Kinematische und dynamische Technikanalyse im Slalom als Grundlage für die Entwicklung skispezifischer Krafttrainingsgeräte und Krafttrainingsmethoden - Raschner, C. (1997)
In the coming years, research into the training will be more than ever before called upon to make suggestions as to the optimization of training methods. In the future, improvements in achievement may be reached by raising the quality of training. In the project at hand a detailed kinematics and kinetic analysis of slalom technique will be pursued in the opening section. For the kinematics analysis, 32 passing points were fixed on the slope and geodesically measured. Two video cameras mounted on platforms could follow the racer in his movements through panning and zooming. The ground reaction forces and pressure distributions on the plantar surface were measured with specially adapted insoles. After the calculation and evaluation of the three-dimensional kinematics data, any desired course insightful to slalom technique could be represented and interpreted. The results of the kinetic measurements brought insightful information about the degree, progression, and distribution of ground reaction forces. In the second part of the project, two pieces of training equipment the ski-power-hometrainer and the ski-power-simulator were developed and built based on the knowledge gained from the earlier results. The goal was to realize the highest possible correspondence between the time, space, and energy features characteristic of competition and training exercise. To check the validity of the training device, the kinematics and kinetic features of the training exercise were analyzed. The comparison of the registered features resulted, with both devices, in a high to very high degree of correspondence to the motion during slalom competition.